Genomic Virulence Features of Two Novel Species Nocardia barduliensis sp. nov. and Nocardia gipuzkoensis sp. nov., Isolated from Patients with Chronic Pulmonary Diseases - Nouioui, Imen; Cortés-Albayay, Carlos; Neumann-Schaal, Meina; Vicente, Diego; Cilla, Gustavo; Klenk, Hans-Peter; Marimón, Jose María; Ercibengoa, Maria (Microorganisms (Basel), 2020)
Strains 335427T and 234509T, isolated from two 76-year-old patients with chronic pulmonary diseases, were the subject of polyphasic taxonomic studies and comparative genomic analyses for virulence factors. The 16 rRNA gene sequence similarity between strains 335427T and 234509T and their closest phylogenetic neighbors Nocardia asiatica NBRC 100129T and Nocardia abscessus NBRC 100374T were 99.5% and 100%, respectively. Digital DNA–DNA hybridization values between the aforementioned studied strains were well below the 70% threshold for assigning prokaryotic strains to a novel species. Strains 335427T and 234509T have genome sizes of 8.49 Mpb and 8.07 Mpb, respectively, with G + C content of 68.5%. Isolate 335427T has C16:0, C18:1 ω9c, C18:0 and C18:0 10 methyl as major fatty acids (>15%) and mycolic acids formed of 52–54 carbon atoms. However, only C18:1 ω9c was detected for isolate 234509T, which had mycolic acids with 44–56 carbon. Based on phenotypic and genetic data, strains 335427T (DSM 109819T = CECT 9924T) and 234509T (DSM 111366T = CECT 30129T) merit recognition as novel species, which are named Nocardia barduliensis sp. nov. and Nocardia gipuzkoensis sp. nov., respectively. All the strains studied had homologous VF-associated genes to those described in M. tuberculosis, including experimentally verified virulence genes in humans related to tuberculosis. The narGHIJ (nitrate reduction pathway) and gvpAFGOJLMK (gas vesicles) genetic maps of strains 335427T, 234509T, NBRC 100129T and NBRC 100374T showed the same syntenic block and raise the question of whether their functions are interlinked during the infection of the human host. However, further research is required to decipher the role of the gas vesicle in the pathogenicity mechanism of Nocardia spp.